1999
DOI: 10.1152/ajpheart.1999.277.6.h2247
|View full text |Cite
|
Sign up to set email alerts
|

Human VEGF gene expression in skeletal muscle: effect of acute normoxic and hypoxic exercise

Abstract: Vascular endothelial growth factor (VEGF) is involved in extracellular matrix changes and endothelial cell proliferation, both of which are precursors to new capillary growth. Angiogenesis is a vital adaptation to exercise training, and the exercise-induced reduction in intracellular PO2 has been proposed as a stimulus for this process. Thus we studied muscle cell PO2 [myoglobin PO2 (MbPO2)] during exercise in normoxia and in hypoxia (12% O2) and studied the mRNA levels of VEGF in six untrained subjects after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
159
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(172 citation statements)
references
References 22 publications
11
159
2
Order By: Relevance
“…Studies on the regulation of capillarization in response to exercise and training have shown that acute exercise enhances the protein and mRNA levels of several angiogenic factors such as vascular endothelial growth factor (VEGF) (21,31), matrix metalloproteinase-2 (MMP-2) (6,15), and endothelial nitric oxide synthase (eNOS) (11,34). In addition, acute exercise has been shown to cause an increase in the muscle interstitial concentration of VEGF (18,21), which, at least in part, appears to reflect a release of VEGF from skeletal muscle cells as demonstrated in cultured muscle cells (22).…”
mentioning
confidence: 99%
“…Studies on the regulation of capillarization in response to exercise and training have shown that acute exercise enhances the protein and mRNA levels of several angiogenic factors such as vascular endothelial growth factor (VEGF) (21,31), matrix metalloproteinase-2 (MMP-2) (6,15), and endothelial nitric oxide synthase (eNOS) (11,34). In addition, acute exercise has been shown to cause an increase in the muscle interstitial concentration of VEGF (18,21), which, at least in part, appears to reflect a release of VEGF from skeletal muscle cells as demonstrated in cultured muscle cells (22).…”
mentioning
confidence: 99%
“…Multiple signals generated during exercise, including mechanical events associated with muscle contraction and reduced muscle intracellular oxygen tension, have the potential to regulate vascular endothelial growth factor (VEGF) gene expression (6,28,29). VEGF is a well-known, potent angiogenic factor, which also functions as a vascular permeability and endothelial cell survival factor (13).…”
mentioning
confidence: 99%
“…VEGF mRNA levels have been reported to increase with hypoxia in mouse brain (ChĂĄvez et al, 2000;Kuo et al, 1999) but also to decrease in rat muscle (Olfert et al, 2001b). In human muscle, VEGF is increased with acute exercise (Gustafsson et al, 2002;Richardson et al, 1999). However, it has not previously been studied whether VEGF expression is increased in human muscle in response to hypoxia, and simultaneous determination of these signalling factors and morphological characterization of capillary density in human skeletal muscle has not previously been performed in lowlanders acclimatizing to altitude or in high-altitude natives.…”
mentioning
confidence: 99%